Dynamic Changes in Maritime Research Capability in Chinese Universities - Young-Tae Chang; Ahhyun Jo; Kyoung-Suk Choi (Journal of Advanced Transportation)
This study determines the top fifty authors in China and their university affiliations in the maritime transportation field, compared to their world ranking. We refer to China in the broad sense of the Chinese economies, including not only mainland China and Hong Kong, but also Chinese Taipei (Taiwan) and Singapore. This study analyzes sixty-five SSCI and SCI journals in the field of maritime and transportation between the years 2000 and 2015. In terms of ranking, three indicators are employed: total number of articles, weighted score (indication of author contribution), and the impact score. With the exception of Shanghai Jiao Tong University, no other universities selected in the first phase of Project 985, which received billions of dollars in government support/aid, were listed in the world ranking. Star authors are deemed to have contributed greatly to the rankings of their affiliated universities. The future of China’s rankings is bright in view of the increasing number of papers being published by Chinese authors and universities and their strong grounding in quantitative methodologies.